IMPROVING THE STUDENTS’ READING COMPREHENSION THROUGH “TELLS” STRATEGY AT THE FIRST YEAR STUDENTS OF SMA MUHAMMADIYAH 9 PERUMNAS MAKASSAR - Ilmiah Ilmiah; Abd Mustakim (Universitas Muhammadiyah Makassar, 2013)
This research aimed to improve students’ reading comprehension by using the strategy of title, examine, look, look and setting. This research used Classroom Action Research (CAR) by implementing two cycles (cycle 1 and 2). This research tried to find out the students’ achievement in literal comprehension through TELLS Strategy and the students’ achievement in interpretive comprehension through TELLS Strategy. Then the researcher found the results based on the goals of the research, those were the students’ improvement in literal reading comprehension was 67.75% from 51.31%, as well as the students’ improvement in interpretative reading comprehension 67.10% from 51.31%. It was reached by the implementation of TELLS Strategy in the classroom.Keywords: Reading, TELLS Strategy, CAR, Literal, Interpretative.